2001
DOI: 10.1074/jbc.m010499200
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Stimulates Proliferation and Survival of Human Breast Cancer Cells through Two Distinct Signaling Pathways

Abstract: We show here that the neurotrophin nerve growth factor (NGF), which has been shown to be a mitogen for breast cancer cells, also stimulates cell survival through a distinct signaling pathway. Breast cancer cell lines (MCF-7, T47-D, BT-20, and MDA-MB-231) were found to express both types of NGF receptors: p140 trkA and p75 NTR . The two other tyrosine kinase receptors for neurotrophins, TrkB and TrkC, were not expressed. The mitogenic effect of NGF on breast cancer cells required the tyrosine kinase activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
213
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(221 citation statements)
references
References 40 publications
(42 reference statements)
5
213
0
3
Order By: Relevance
“…For phosphorylated TrkA, a mouse monoclonal anti-p-TrkA antibody (sc-8058, Santa Cruz Biotechnology Inc.) (diluted 1 : 200) was used. Lysate from the breast cancer cell line MCF-7 was used as a positive control for NGF (Dolle et al, 2003), TrkA, and p75NTR (Descamps et al, 2001b).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…For phosphorylated TrkA, a mouse monoclonal anti-p-TrkA antibody (sc-8058, Santa Cruz Biotechnology Inc.) (diluted 1 : 200) was used. Lysate from the breast cancer cell line MCF-7 was used as a positive control for NGF (Dolle et al, 2003), TrkA, and p75NTR (Descamps et al, 2001b).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…14 However, the ratio between NGF:NGFR was reported to be of prognostic significance. 15 As the role of NGFR in breast cancer development and progression is not fully understood and conflicting results have been reported, [14][15][16][17] we decided to investigate the distribution of NGFR in breast tissue from various benign and malignant conditions and explore potential prognostic relationships. In a preliminary analysis, we and others 5 observed that NGFR showed a peculiar distribution, being restricted to myoepithelial cells, intralobular fibroblasts of terminal duct-lobular units, perivascular cells (vascular adventitia) and nerve bundles.…”
mentioning
confidence: 99%
“…p75NGFR is a member of the TNFR superfamily and has been shown to be a conditional tumor-suppressor gene (19). In breast cancer and melanoma, p75NGFR acts as an oncogene, increasing cell proliferation, survival, and migration (6,(20)(21)(22). In contrast, in prostate cancer and neuroblastoma, p75NGFR acts as a tumor-suppressor gene, inducing apoptosis and inhibiting cell proliferation and invasion (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%